Evaluating the Efficiency of Emergency Response System During Disaster Incidents in Niger State, Nigeria (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2026)
Despite the presence of state emergency management agency in Niger State, there are still challenges in emergency response, which hinders the efficiency and effectiveness of disaster recovery. Without efficient response system, emergency agencies may struggle to make informed decisions, and coordinate response efforts effectively. The effectiveness of disaster recovery efforts during disaster incidents relies on the availability, accessibility, and utilization of accurate and timely response by emergency management agencies. Additionally, inadequate evaluation can lead to delays in disaster recovery, miscommunication among agencies, and ultimately hinder the achievement of disaster management goals. In recent time, disaster related risk have been exacerbated by climate change and this has impacted progress toward sustainable development. Although the Niger state government has worked assiduously to strengthen her disaster risk management strategy by establishing Niger State Emergency Management Agency (NSEMA). It is hitherto regrettable that such idea has not yielded such progress as event continue to threaten the existence, wellbeing and safety of the population. It is disheartening that the State has continually experience humanitarian emergency and catastrophes on an ever-increasing scale and frequency, and it has become so difficult for the affected persons and community to adsorb and recover from the impact created by these disasters. Therefore, it has been observed that disasters signal the failure of a society to adapt successfully to certain features of its natural and socially constructed environment in a sustainable fashion. In view of the foregoing ,the study concludes that there is need for the state to improve its effort at creating sustainable measures that will help protect its citizens from natural and man-made disasters and also have a walkable data base that can be used to assess the damage caused by disaster and proffer avoidable solutions proactively. The study suggested that the state government should as a matter of utmost urgency constitute a body of experts in disaster risk management for the purpose of mitigating the effect of this disasters that has become a recurring decima in the state.